Perbedaan Kemandirian Perilaku Pada Remaja di Lihat Dari Pola Asuh Orang Tua Tunggal di Kecamatan Telanaipura - Sulis Indriyani; Akmal Sutja; Hera Wahyuni (Journal on Education, 2023)
Recently, there has been a stigma that children who grow up from single parents are naughty, controlled and carry other negative meanings. Parenting style is very influential in the formation of children's character, one of which is in the formation of independent behavior in children. The purpose of this study was to determine the quality of behavioral independence in children and differences in the influence of single parenting styles on behavioral independence in children. Meanwhile, the intended behavior independence is changes in decision-making, changes in susceptibility to the influence, and changes in feeling of self-relience. This type of research is a comparative quantitative research with a total sample of 70 respondents obtained from sampling using purposive sampling technique. The data collection technique used in this study was a questionnaire and the data analysis technique used was the one way ANOVA test and the independent t-test. Based on the research, it was found that democratic parenting was more dominantly applied in child rearing with an average level of 73.98%, while the average level of behavior independence in adolescents was 63.64% and included in the medium category. Based on the one way ANOVA test conducted, the asomtatic asignificance value was 0.08 <0.05 so that it can be interpreted that there is a difference in independence in adolescents when viewed from single parent parenting in Telanaipura District. Furthermore, from the results of the independent t-test, it was found that children with democratic parenting styles had the highest level of independence in behavior when compared to other parenting styles.